Scattering for Semilinear Wave Equation with Small Data in High Space Dimensions (Journal of Partial Differential Equations, 1999)
In this paper we study the scattering theory for the semilincar wave equation u_{tt} - Δu = F(u(t, x), Du(t, x)) in R^n (n ≥ 4) with smooth and small data. We show that the scattering operator exists for the nonlinear term F = F(λ) = O(|λ|^{1, α}), where α is an integer and satisfies α ≥ 2, n = 4; α ≥ I, n ≥ 5.
Keywords: Semilinear wave equation; scattering; asymptotic behavior